2017
DOI: 10.1007/s10815-017-1023-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of angiogenic markers in adverse perinatal outcomes: fresh versus frozen embryo transfers

Abstract: Fresh transfers were associated with lower birth weight infants compared to frozen transfers. While there was no difference in sFlt-1:PlGF ratios between fresh and frozen transfers, these ratios were significantly lower in SGA infants, suggesting an imbalance in angiogenic markers during placentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…In FET in a natural cycle, a more physiological uterine environment and better regulation of angiogenesis during the placentation process is predicted than in fresh ET. However, Woo et al [14] found no difference in sFlt-1:PlGF ratios at 5 weeks of gestation between fresh ET and frozen FET. They suggest that the altered uterine hormonal milieu in fresh embryo transfers does not influence the angiogenic factors and that these factors do not drive early placentation [14].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In FET in a natural cycle, a more physiological uterine environment and better regulation of angiogenesis during the placentation process is predicted than in fresh ET. However, Woo et al [14] found no difference in sFlt-1:PlGF ratios at 5 weeks of gestation between fresh ET and frozen FET. They suggest that the altered uterine hormonal milieu in fresh embryo transfers does not influence the angiogenic factors and that these factors do not drive early placentation [14].…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, there is a possibility that freezing and thawing damage the trophoblast and thereby negatively influence this process and biomarker production. Only a few studies have specifically considered the differences in biochemical marker levels between pregnancies conceived after FET compared to fresh ET and presented inconclusive results [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the fact that the process of angiogenesis is regulated by numerous pro-angiogenic and anti-angiogenic factors and cytokines as well as angiogenic receptors, there is an increasing number of studies focusing on the balance between pro-angiogenic and anti-angiogenic factors in preeclampsia [ 143 , 144 ]. In some studies, the ratios sFlt-1/PlGF and VEGF/ sFlt-1 were determined to study the association of angiogenesis with certain pathological conditions [ 19 , 21 , 145 ].…”
Section: Vegf In Reproductive Failurementioning
confidence: 99%
“…With a higher affinity but lower kinase activity, VEGFR-1 acts more like a decoy, a negative regulator of VEGF [ 14 , 15 ]. sVEGFR-1 (sFlt-1), a soluble form of VEGFR-1, can also trap VEGF, VEGF-B, and PlGF and therefore block their binding to membrane receptors [ 16 , 17 ], and its activity has been proven to be strongly correlated with unexplained infertility [ 18 , 19 ], recurrent miscarriage [ 20 ], and adverse pregnancy outcomes [ 21 ]. PlGF, which shows lower affinity for VEGFR-1 than VEGF [ 22 ], can replace VEGF in the VEGFR-1 “sink” and thus potentiate the angiogenic effect of VEGF, since VEGFR-2 is the main receptor with a pro-angiogenesis effect [ 4 , 12 ].…”
Section: Introductionmentioning
confidence: 99%